Pengaruh manajemen aset daerah terhadap optimalisasi pengelolaan aset daerah Provinsi Bengkulu - Rolly, Venni Lorenzo; Arnova, Iwin; Herawati, Helmi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The purpose of this research is to ascertain how regional asset management affects regional asset management optimization in Bengkulu Province. Tests in this review utilize acquainted research techniques. The participants in this study were all members of the BPKAD of Bengkulu Province's Business and Asset Management Bureau. In this study, multiple linear regression analysis was used to analyze the data. The goal of this regression analysis is to get a complete picture of how the dependent variable and the independent variables are related.